Relationship Of Professionalism With Religious Moderation In Islamic Religious Education Teachers - Khairuddin Hasan (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2020)
This study aims to reveal the relationship between teacher professionalism and religious moderation. Professionalism is one of the four competencies that teachers must have in addition to pedagogical competence, personality competence, and social competence. The research location was in Medan City with respondents from Islamic religious education teachers. This type of research is field research using a quantitative approach. Hypothesis testing analysis uses nonparametric statistics with the Spearman rank formula because the research data is in the form of an ordinal scale. The results showed that there was a very weak relationship between professionalism and religious moderation in teachers with a correlation coefficient of 0.116. The relationship between variables is also not significant with the Sig. (2-tailed) 0.750 which is greater than 0.05. There is a unidirectional relationship between variables with the meaning that if teacher professionalism increases, religious moderation in teachers also increases, and vice versa if teacher professionalism decreases then teacher religious moderation also decreases